(untitled) (Archives of Criminology, 2025)
Polish victimology primarily focuses on the rights and procedural guarantees of victims, while less often giving voice to the victims themselves. In this article, we aim to present the perspectives of victims and to describe their needs and expectations regarding the justice system. The article is one of three texts (cf. Kopeć, Woźniakowska, Wzorek 2025; Francuzik, Szulecka 2025) presenting an evaluation of a pilot victim support program implemented by the Foundation for the Assistance of Crime Victims and the Emergency Service for Victims of Domestic Violence, “Niebieska Linia.” The evaluation involved interviews with victims of violence in close relationships, representatives of the justice system, and victim support professionals. We show that victims perceive the justice system as a complex whole. Their key needs and expectations include being heard, having their harm acknowledged, and feeling safe.